Influence of terms of fabrication on electrical and photoelectric properties of photocell on base of Schottky barrier contact Pd-n-GaAs - A. I. Blesman; R. B. Burlakov (Омский научный вестник)
Structure and strategy of the fabrication of the photocell on the base of the Schottky barrier contact Pd-n-GaAs are сonsidered. There is measured I(V)-features of photocells, their C-V-features, spectrums photovoltage and current of the short circuit, and determined height of the Schottky barrier contacts Pd-n-n+-GaAs by photoelectric method. There is shown that air annealing of structures n-n+-GaAs-AuGe under (200–210) C within 30 minutes before precipitating a film Pd on n-GaAs brings: to the reduction on two orders direct Idir and inverse Iinv currents (under 0,5 V), to reduction on three orders of density of the current of the saturation J0 , to reduction of capacities of photocells before values (241– 233) pF under inverse tensions (0,22–0,96) V, reduction of the current of the short circuit of photocells and to increase their photovoltage that connected with formation fine insulator film on n-GaAs under air annealing of structures n-n+-GaAs-AuGe.